Getrenntes zusammenbringen. Blicke auf das Alte Testament und das Judentum (1524-1939) - Ahuis, Ferdinand (Arbeiten zur Kirchengeschichte Hamburgs, 2018)
In the 17th and 18th centuries, Hamburg was one of the strongholds of European Hebrew studies in Hamburg. The Academic Gymnasium, founded in 1613, created professorships for Hebraic studies or - more comprehensively - for Oriental studies. Names like Hermann Samuel Reimarus are associated with them. Some of these teachers also became the main pastors.Graduated exegete of Old Testament and retired main pastor of the all curch St. Nikolai of Hamburg Ferdinand Ahuis has investigated the legacies of nine of his predecessors from four centuries with regard to their attitude towards Judaism. In this work, he presents their theological interpretations of the Old Testament which have influenced the Christian view of Judaism.The work concludes with a virtual dialogue between the main pastor and biblical scholar Heinz Beckmann and the rabbi and biblical scholar Benno Jacob.